Is Democracy Really the Best Medicine? - How different regimes react to pandemics - Lins, Rodrigo (2020)
Pandemics are nothing new to humans. From the Plague of Justinian to the current Covid-19,the world has seen all sorts of contagious diseases. But do different political regimes react differently? We argue that the political regime has no major influence. More specifically: democratic and autocratic regimes have similar performances in taking action to combat the disease. The reasoning for this, however, vary. We do believe that the volatility is higher within the authoritarian group. To test this hypothesis, we will conduct a survival analysis, having the adoption of a strict social isolation policy as the event of interest. We will control for institutional variables, such as the presence of local governments; and for other social variables, such as population density. We will also take in consideration previous experience with SARS. Our findings corroborate our hypothesis. The difference between the two types of regime is not statistically significant. The economy, however, seems to play small role: The wealthier the country is, the longer it takes to adopt restriction measures.